Exploring the influence of social media on digital reputation and e-commerce: Insights from Saudi SMEs - Alshamrani, Nada (Edelweiss Applied Science and Technology, 2025)
This study examines the influence of social media platforms on the online reputation of small and medium-sized enterprises (SMEs) in Saudi Arabia, with a broader focus on their impact on e-commerce. Additionally, it explores the strategies SMEs employ to effectively manage their online reputation across different social media platforms. A qualitative, interview-based approach was utilized to gain deeper insights into the response strategies adopted by SMEs on social media. Interviews were conducted with experts from Saudi SMEs, and thematic analysis was applied to interpret the collected data. The study highlights key strategies businesses use to build and maintain their online reputation on social media. The thematic analysis provides practical guidance for SMEs on effectively leveraging social media platforms to enhance their digital presence and engagement. This research aims to advance the understanding of online reputation and its significant role in shaping business success, particularly for SMEs. By identifying effective strategies, the study contributes to the broader discussion on digital reputation management in the e-commerce sector.